Damage identification based on vibration measurements applied to masonry structures - Ramos, Luís F. (2006)
The present paper aims to explore damage assessment in the masonry structures at an early stage by vibration measurements. Two replicates of historical constructions were built in virgin state: one arch with 1.5 m span and one shear wall with 1.0 m2. Afterwards, progressive damage was applied and sequential modal identification analysis was performed at each damage stage, aiming to find adequate correspondence between dynamic behavior and internal crack growth. Accelerations and strains in many points were record in the replicates. Eigen frequencies, mode shapes and modal strains were derived from the dynamic measurements. Environmental effects of the temperature and relative humidity on the dynamic response were studied. A first updating process was performed on the results of the undamaged arch to tune a finite element model. Moreover, the tests were repeated with added masses to scale the mode shapes. Finally, a brief analysis of the results of the several damage scenarios are presented in the paper